RAMAN SPECTRA AND STRUCTURE OF BAO-SIO2, SRO-SIO2 AND CAO-SIO2 MELTS TO 1600°C - Frantz J.D.; Mysen B.O. (My University, 1995)
Raman spectra were collected for barium silicate, strontium silicate and calcium silicate melts at temperatures ranging from the glass transition region to temperatures as high as 1600°C. For melts less polymrized than disilicate, the spectra were used to determine the relative abundances of the Q3, Q2 and Q1 tetrahedra and the Si2O2-5, SiO2-3 and Si2O6-77 structural units in the melts. A concentration constant was computed for the reaction: 4SiO2-3 # Si2O2-5 + Si2O6-7 and was found to vary with composition from approximately log10 Kc = 0.5 for barium silicate melts with NBO/Si = 1.143 to log10 Kc = -1.75 for calcium metasilicate melts with NBO/Si = 2. Little difference was found to exist in the structural behavior of the melts on the three alkaline-earth silicate binary joins. Activity coefficients were computed for the SiO2-3 structural unit as a function of bulk composition. The logarithm of the activity coefficients and mole fraction of the structural unit are linearly correlated.